DISEMINASI DAKWAH ERA DISRUPSI 4.0 DAN LITERASI MEDIA SOSIAL (PERSPEKTIF JURNALISME PROFETIK) - Firdaus Muhammad (Fakultas Dakwah dan Komunikasi, 2019)
The flow of information through social media (social media) also influences people's behaviour. The rise of various news in social media which leads to religious propaganda is increasingly difficult to stem. Propaganda in communication or media studies does not always have a negative connotation. But in this discussion, propaganda is more directed at the provocation dimension, precisely the issue of religion becomes propaganda or politicized by elites and hoaxes spreaders to provoke the people with massive information distribution.